The Greening of Euro 2016: Fan Footage, Representational Tropes, and the Media Lionization of the Irish in France. (January 2019) - O'Boyle, Neil; Kearns, Colm
This article considers the representation of Irish identity in the media-sport discourse surrounding Euro 2016 in France. The behavior of Irish football fans attracted considerable attention in both the domestic and international media, and they were praised for their friendliness, helpfulness, and goodwill while in France. This media lionization eventually culminated in the Irish fans being awarded (jointly with their Northern Irish neighbors) the Medal of the City of Paris in July 2016. In this article, we examine how fan footage, taken on smartphones and uploaded to the video-hosting site YouTube (mostly by Irish fans themselves), featured centrally in news coverage of the tournament and fed a wider discourse about Irish identity, which relied on longstanding representational tropes. In concluding the article, we reflect on the paratextual significance of Euro 2016 for the Irish football team's corporate sponsor Three, and more broadly, for Ireland as a nation brand.